Factors contributing the delay in claim settlement towards motor insurance claim / Mustaizah Mohd Ghazi - Mohd Ghazi, Mustaizah (Faculty of Business and Management, 2011)
This study is designed to identify the factors contributing the delay in claim settlement toward motor insurance. Under this research study, the independent variables are dispute in compensation, claim documentation and improper claim management. While, the dependent variable delay in motor insurance claim settlement. The objective of this study are to identify the major factor that contributes to the delay of motor claim settlement and to identify the significant relationship between the factors contributing to the delay in claim settlement towards motor insurance claim with the independent variable. The data set in this research study are collected from the resident in Kampung Attap. The 100 respondents become the sample in this research study by answering the questionnaires. The findings has show that two out of three independent variable which is dispute in compensation and claim documentation have significant relationship with delay in motor insurance claim settlement. While, only improper claim management give no significant relationship in this research study. There are also several recommendation that researcher suggest on the finding founds.